Bencana Alam, Tanggungjawab Pemerintah dan Persoalan Agraria - Ifdhal Kasim (Unisia, 2005)
The universe disasters including earthquake certainly will occur because we live at the regions that potential to happen earthquake, the regions along Pacific instead, known as ring of fire because of the earth is still and will move continuosely. For that reason, there is no choice that we can do except to anticipate, to build a proof-earthquake building. Govemment has decided that the planning  to solve Aceh and North Sumatra disasters will conduct three steps program: the emergency program that will be conducted for one year, in this stage, the aids will be directed especially dresses, food and health aids